Travel to Barcelona, city that still belongs to Spain - Petrică Ştefan; Florina Ştefan; Romeo Cătălin Creţu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
For more than 20 years, <<Turisme de Barcelona>> has been compiling indicators about tourist activity in the city based on fieldwork carried out in house and already existing sources. The main results are obtained by conducting surveys of hotel managers and tourists visiting the city. The data generated has been gathered in reports and publications since 1989. The multiplier effect of tourism on the economy of the Barcelona city and the province is very significant: 25% of the impact affects sectors not directly considered as tourism. In terms of demand, the variety of profiles is very wide, which helps reduce seasonality in activity during the week and throughout the year. Tourism in Barcelona is characterised by a wide variety of departure origins and by its international market trends, which has not stopped growing: 80% of tourism demand comes from overseas markets. In doing so, we've concentrated on answering your most important questions on transport, accommodation, activities and attractions.
Keywords: 330; grow; heritage; province; travel; tourism